Formação em residência multiprofissional e a atuação na atenção básica em saúde: um estudo em serviços públicos municipais da região sul do Brasil - Miolo, Silvana Basso (2018)
Objective: To demonstrate the potential of training and participation of health professions not included in current Primary Care teams from the conception of professionals involved in Multiprofessional Health Residency Programs developed in municipal public services at Southern Brazil. Materials and methods: This is a cross-sectional, exploratory, descriptive study with qualitative-quantitative analysis. Data were collected from May to September 2016 through an electronic questionnaire available in Google Drive, consisting of closed and open questions, considering the relationship of Multiprofessional Health Residency Programs for Primary Care, provided by the National Commission of Multiprofessional Residency in Health; subsequently, Coordinators of the aforementioned Programs were contacted in order to authorize the research by sending the e-mail list of their Tutors, Preceptors, Second Year Residents, Egresses and Dropouts, to which the questionnaire composed of items that made possible sociodemographic identification and professional training of the participants were sent, as well as it was possible to understand the vision of participants and also their views on the participation of other professions other than Nursing and Medicine, traditional areas that make up the minimum teams of Primary Health Care. The information obtained from open questions was approached by the technique of content analysis by Bardin. Results: A total of 100 professionals participated in this study: one Coordinator, four Coordinators/Tutors, 19 Tutors, 14 Preceptors, 22 Residents, 37 Egresses, 3 Dropouts; 31% belong to the professional category of nurses, 13% of dental surgeons, 12% of psychologists, 9% of pharmacists, 7% for professional categories of social assistants, physical educators, speech therapists and nutritionists, 5% physiotherapists and 1% occupational therapist and veterinarian. The female sex predominated (89%). The mean age of all subjects was 33.19 years. Regarding the professional qualification of the teaching and assistance staff of Multiprofessional Health Residency Programs, 80% of Coordinators and 84.2% of Tutors were trained for Collective Health, Public Health or Higher Education. In the same way, 92.9% of Preceptors have at least one specialization that contemplates these subjects. For 50% of Residents, Egresses and Dropouts, the preparation for Primary Health Care during graduation was insufficient, others considered: 19.3% sufficient, 16.1% precarious, 13% adequate and 1.61% full. Regarding Egresses, 45.9% considered that the Multiprofessional Residency Program fully and 35.1% adequately contributed for their personal and professional formation. Dropout left the residence because they began working. Most professionals 63% stated that other professionals, in addition to nurses and physicians, should compose the teams for Primary Care, appearing as categories - epidemiology and linkage with, 31% reiterated their participation in family health support modality and 6% have chosen both. Regarding Pedagogical Projects, Tutors and Preceptors attributed the lack of time and the teaching-service relationship as the greatest difficulties to perform their functions. Final Considerations: The Residency Programs were powerful trainers of health professionals to work in Primary Care. They provided experiences in Primary Care that allowed participants from different professions to reflect that the current model at the time of data collection, Support Centers for Family Health, does not have the power to transform the reality of health conditions to Brazilian population. It is defended new guidelines for organization and participation of different professions in Primary Care, expanding the basic team within other professionals, so that they can provide direct care to users. In this sense, Multiprofessional Residency Programs are reinforcers, on the one hand, of a new professional formation in health and, on the other hand, of the current organizational proposal.